2018
DOI: 10.1080/10942912.2018.1439958
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental validation of antioxidant properties of synthesized bioactive ferulic acid derivatives

Abstract: Ferulic acid, a well-known natural phenolic compound, is considerably reported for its hydroxyl and peroxyl radical scavenging activities. However, the antioxidant capacity of ferulic acid is limited by its relatively low solubility in hydrophobic media thereby preventing its application for autoxidation of fats and oils. To this end, several research efforts are being made to maximize the therapeutic benefits of ferulic acid and these efforts included but not limited to structural modification of ferulic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Clearly, the RSA(1) values are slightly lower for t-FEF77. This result is consistent with previous studies, where it has been shown that FA was more effective than the urethane amide derivative [9] or a tyrosine-amide derivative [18] in scavenging DPPH radicals. Since the lower antioxidant efficiency of monophenol rings has been well established in literature [19,20], we decided to carry out the experiments for a longer time, in order to evaluate the contribution of the additional monophenolic groups present in FEF77.…”
Section: Antioxidant Activity Of Fa T-fef77 and C-fef77 241 Dpphsupporting
confidence: 93%
See 2 more Smart Citations
“…Clearly, the RSA(1) values are slightly lower for t-FEF77. This result is consistent with previous studies, where it has been shown that FA was more effective than the urethane amide derivative [9] or a tyrosine-amide derivative [18] in scavenging DPPH radicals. Since the lower antioxidant efficiency of monophenol rings has been well established in literature [19,20], we decided to carry out the experiments for a longer time, in order to evaluate the contribution of the additional monophenolic groups present in FEF77.…”
Section: Antioxidant Activity Of Fa T-fef77 and C-fef77 241 Dpphsupporting
confidence: 93%
“…FA contains a methoxy group and a propenoic acid moiety at the ortho and para positions of phenol, respectively. The electron-donating methoxy group might be responsible for the increased antioxidant activity of FA with respect to 4-hydroxycinnamic acid, while the E double bond of the propenoic group might play a responsible role in the stabilization of the phenoxyl radical by resonance [ 9 ]. Although several natural phenols containing a catechol, or a pyrogallol type rings, present high radical scavenging activity in vitro, their high susceptibility to oxidation makes their half-life in the body strongly reduced and therefore their applicability as active pharmaceutical ingredients limited [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant capacity of FA is enabled by its hydroxy and phenoxy groups, which can directly scavenge O 2 ‐ , HO·, and H 2 O 2 via a one electron transfer reaction (Hasanein et al., 2018). Also, unsaturated double bond in the structure of FA can offer an additional protection for cell membrane against harmful ROS (Adeyemi et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the demand for antioxidants in various manufacturing processes, particularly the food industry, has been on the increase, leading to the production of synthetic antioxidants to match this demand. However, in recent years, there has been a shift from synthetic to natural antioxidants (Adeyemi et al, 2018). The preference for the use of natural antioxidants stems from the belief that they have lower toxicity than their synthetic counterparts.…”
Section: Introductionmentioning
confidence: 99%